(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The Urban space is a location where the most significant social evolution is taking place under the influence of the processes of globalization. The city’s analysis in the era of globalization integrates a set of issues related to urban space in the modern global city and the city in conditions of globalization. Global tendencies are re-actualizing the issue of the urban lifestyle of both the individual and the group. The focus of the paper is directed towards detecting globalization precisely in the sphere of the urban, following the changes and the functionality of the space. The urban space is a scene of stratification processes, but also a scene of interweaving different cultures, a result of multiculturalism and multi-confessionalism. On the other hand, layered affiliation leaves an extra mark and recognition. Urban living is a multidimensional phenomenon that can be perceived in many aspects. It is integrating manifestations and urban spectacles, which build a dynamically evolutionary component of space. In a word, the space is the only place in which all the positive but also the negative experiences are being felt by the individual and also by the group. Urban space is a real site for human creativity, acting and using leisure time.